An energy consumption evaluation for existing, commercial buildings - Damron, Lauren Leigh Brannom (Kansas State University, 2017)
The intent of this report is to recommend a process for legislation that can be used to identify commercial buildings that have the greatest potential to reduce energy consumption. A point-based evaluation is completed of current energy processes for existing commercial buildings. The recommended energy evaluation system is applied to an existing building, which allows for a detailed review of how the evaluation is completed for a building. The results are presented to display the value of assessing building energy performance. Additionally, the results reinforce the potential to transform the industry and energy use by buildings.
Keywords: Commercial Building; Energy Consumption; Energy Certification; ASHRAE; Energy Star; LEED; Green Globes; Energy Asset Score